Institutional Quality Assurance and Academic Excellence: An Evaluation of Quality Management Systems in Universities - Ahmad Al-Furqoni; Elen Petrov (International Journal of Post Axial: Futuristic Teaching and Learning, 2026)
Institutional quality assurance has become an essential component in maintaining and improving academic standards in higher education institutions. This study aims to evaluate the implementation of institutional quality assurance systems and their contribution to achieving academic excellence in universities. The research employed a qualitative descriptive approach involving university administrators, quality assurance officers, and academic staff who were directly engaged in quality management processes. Data were collected through semi-structured interviews, document analysis, and observations of institutional quality assurance activities. The collected data were analyzed using thematic analysis to identify key patterns and factors influencing the effectiveness of quality management systems in higher education. The findings reveal that institutional quality assurance systems significantly contribute to improving academic governance, monitoring teaching effectiveness, and supporting continuous institutional improvement. The study also identifies several key factors influencing the success of quality assurance implementation, including leadership commitment, faculty participation, student feedback mechanisms, and effective documentation systems. However, the research also highlights several challenges, such as administrative workload and limited professional training related to quality management practices. Overall, the results suggest that effective institutional quality assurance systems can strengthen academic performance, promote transparency in institutional governance, and support sustainable academic excellence in universities.